A third species of Gegeneophis Peters (Amphibia: Gymnophiona: Indotyphlidae) lacking secondary annular grooves - Kotharambath, Ramachandran; Gower, David J.; Oommen, Oommen V.; Wilkinson, Mark (Zootaxa, 2012)
A new species of indotyphlid caecilian amphibian, Gegeneophis primus sp. nov., is described based on a series of eight speci-mens from the state of Kerala in the southern region of the Western Ghats, India. This species is distinguished from all otherGegeneophis, except G. seshachari and G. pareshi, in lacking secondary annular grooves and scales. It differs from G. ses-hachari and G. pareshi in several features, including having fewer primary annuli and lacking a well-developed unsegmented terminal shield.